Chondrodysplasia and growth failure in children after early hematopoietic stem cell transplantation for non‐oncologic disorders. Issue 2 (4th January 2021) - Botto, Lorenzo D.; Meeths, Marie; Campos‐Xavier, Belinda; Bergamaschi, Rosalba; Mazzanti, Laura; Scarano, Emanuela; Finocchi, Andrea; Cancrini, Caterina; Zirn, Birgit; Kühnle, Ingrid; Kramm, Christof Maria; Alanay, Yasemin; et al.
Abstract: Bone dysplasias (osteochondrodysplasias) are a large group of conditions associated with short stature, skeletal disproportion, and radiographic abnormalities of skeletal elements. Nearly all are genetic in origin. We report a series of seven children with similar findings of chondrodysplasia and growth failure following early hematopoietic stem cell transplantation (HSCT) for pediatric non‐oncologic disease: hemophagocytic lymphohistiocytosis or HLH (five children, three with biallelic HLH‐associated variants [in PRF1 and UNC13D ] and one with HLH secondary to visceral Leishmaniasis), one child with severe combined immunodeficiency and one with Omenn syndrome (both children had biallelic RAG1 pathogenic variants). All children had normal growth and no sign of chondrodysplasia at birth and prior to their primary disease. After HSCT, all children developed growth failure, with standard deviation scores for height at or below −3. Radiographically, all children had changes in the spine, metaphyses and epiphyses, compatible with a spondyloepimetaphyseal dysplasia. Genomic sequencing failed to detect pathogenic variants in genes associated with osteochondrodysplasias. We propose that such chondrodysplasia with growth failure is a novel, rare, but clinically important complication following early HSCT for non‐oncologic pediatric diseases. The pathogenesis is unknown but could possibly involve loss or perturbation of the cartilage‐bone stem cell population.